2015
DOI: 10.1159/000369726
|View full text |Cite
|
Sign up to set email alerts
|

WT1 Enhances Proliferation and Impedes Apoptosis in KRAS Mutant NSCLC via Targeting cMyc

Abstract: Background: A novel link between oncogenic KRAS signalling and WT1 was recently identified. We sought to investigate the role of WT1 and KRAS in proliferation and apoptosis. Methods: KRAS mutations and WT1 (cMyc) expression were detected using Sanger sequencing and real-time PCR in 77 patients with non-small cell lung cancer (NSCLC). Overexpression and knockdown of WT1 were generated with plasmid and siRNA via transient transfection technology in H1299 and H1568 cells. MTT assay for detection of cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In NSCLC, WT1 was upregulated in cancer specimens compared with NATs (44). Functional studies revealed that WT1 enhanced cell proliferation, invasion, cisplatin-resistance and decreased apoptosis (44)(45)(46)(47). The present study, in accordance with previous findings, demonstrated that knockdown of WT1 inhibited growth, migration and invasion of NSCLC cells.…”
Section: Discussionsupporting
confidence: 91%
“…In NSCLC, WT1 was upregulated in cancer specimens compared with NATs (44). Functional studies revealed that WT1 enhanced cell proliferation, invasion, cisplatin-resistance and decreased apoptosis (44)(45)(46)(47). The present study, in accordance with previous findings, demonstrated that knockdown of WT1 inhibited growth, migration and invasion of NSCLC cells.…”
Section: Discussionsupporting
confidence: 91%
“…WT1 is a gene regulator important for cell growth, apoptosis, and differentiation, and multiple genes are regulated by WT1. Interestingly, one of the WT1 targets is MYC , which is activated by WT1 but suppressed by a WT1 : BASP1 complex (Goodfellow et al , ; Green et al , ; Han et al , ; Wu et al , ). Recent studies showed that WT1 is activated in pancreatic cancer and that patients with elevated BASP1 levels have a significantly better prognosis than individuals whose cancer cells contain no BASP1 but high WT1 levels (Zhou et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…A third major finding was no increase in CoRL proliferation in RenWt1 fl/fl mice, and enalapril had no effect. This was of interest, as several groups have shown that WT1 enhances proliferation of tumor cells and cardiac endothelial cells ( Li et al., 2015 , Wu et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%